Pengaruh Tingkat Pendapatan dan Gaya Hidup Hedonisme terhadap Kualitas Pengelolaan Keuangan Pribadi Generasi Z di kota Makassar - Hikmayani Subur; Wahyu Muh. Syata (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of income level and hedonistic lifestyle on the quality of personal financial management of Generation Z in Makassar City. The research method is a quantitative approach with data collection techniques through surveys and questionnaires to Generation Z in Makassar City using 100 samples with multiple linear regression data analysis techniques. The results of the study indicate that income level has a positive effect on the quality of personal financial management because the higher the income, the higher the ability of Generation Z to manage personal finances flexibly and more stably. The hedonistic lifestyle on the quality of personal financial management of Generation Z shows a pattern that tends to be negative, where the increasing tendency of hedonism will have an impact on the decreasing ability to manage finances effectively if done excessively, so training and education are recommended for both aspects related to understanding and financial management skills, so that Generation Z is able to balance lifestyle with financial responsibility in order to achieve personal economic stability in the future.